An approach to model the thermal conversion and flight behaviour of Refuse Derived Fuel. (15th July 2017) - Liedmann, B.; Arnold, W.; Krüger, B.; Becker, A.; Krusch, S.; Wirtz, S.; Scherer, V.
Highlights: Numerical models for combustion and flight behavior of RDF are presented. An extensive fraction based fuel analysis was carried out. Drag and lift coefficients were derived by drop-shaft measurements. Characteristic combustion phases and times were determined with a single particle reactor. The numerical models were applied to a full scale industrial boiler simulation. Abstract: The current paper presents a simplified approach which allows the CFD simulation of Refuse Derived Fuel (RDF) combustion. The starting point is the subdivision of a real RDF into characteristic fuel fractions by sorting. Each of the fractions was analyzed concerning elemental composition, heating value, proximate analysis as well as size and shape. The flight behavior of the RDF fractions has been characterized in a drop-shaft. A stereoscopic camera system was used to derive drag and lift coefficients. In addition, a single particle combustion reactor has been used to measure the duration of the relevant combustion phases like volatile combustion or char burn-out. A model calculating the particle trajectories based on the measured drag and lift frequency distributions has been developed. For combustion modelling the RDF has been subdivided into devolatilizing and char forming fractions and into fractions which are converting through a melting and decomposition process. For both types of materials combustion models have been formulated. Intra particle temperature gradients are accounted for. A change of particle shape during combustion is considered using sphericity as a model parameter. The models have finally been introduced into FLUENT by user defined functions. Comparison with drop-shaft measurements and a single particle combustion reactor show that the models formulated can statistically describe the motion and conversion behaviour of RDF with sufficient accuracy. As an example of application, the models were finally used for the CFD simulation of the furnaces of a 612 MW(e) RDF co-fired coal power plant. The results indicate an overall slower reaction rate of RDF compared to coal, resulting in a total conversion of RDF of 83%.